ANALISIS PERAN PENDIDIKAN MORAL UNTUK MENGURANGI AKSI BULLY DI SEKOLAH DASAR - Purnaningtias, Fianolita; Aika, Nuril; Al farisi, Moh. Salman; Sucipto, Ahmad; Putri, Zherin Mei Biana (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
This paper describes the analysis of the role of moral education to reduce bullying in elementary schools. The development of student moral education is very important to do to improve student morale as national identity and character. The application of moral education to students in primary schools is one of the fundamental and deep alternatives to reduce social deviations such as bullying. Bullying is very dangerous for a child’s character. Besides having high intellectuals as the next generation of the nation, it is appropriate to have good morality to support the formation of a nation with a civilized and virtuous nation. Of course this is inseparable from the role of education and educators. The form of deviations in the form of bullying needs special attention, especially in primary schools, therefore teachers must be able to improve the moral education of students so that deviations such as bullying will not occur and the nation’s goals can be achieved